Molecular insights from the crab Neohelice memory model - Romano, Arturo; Freudenthal, Ramiro; Feld, Mariana (Frontiers in Molecular Neuroscience, 2023)
Memory acquisition, formation and maintenance depend on synaptic post-translational machinery and regulation of gene expression triggered by several transduction pathways. In turns, these processes lead to stabilization of synaptic modifications in neurons in the activated circuits. In order to study the molecular mechanisms involved in acquisition and memory, we have taken advantage of the context-signal associative learning and, more recently, the place preference task, of the crab Neohelice granulata. In this model organism, we studied several molecular processes, including activation of extracellular signal-regulated kinase (ERK) and the nuclear factor kappa light chain enhancer of activated B cells (NF-κB) transcription factor, involvement of synaptic proteins such as NMDA receptors and neuroepigenetic regulation of gene expression. All these studies allowed description of key plasticity mechanisms involved in memory, including consolidation, reconsolidation and extinction. This article is aimed at review the most salient findings obtained over decades of research in this memory model.